The problem of developing the culture of professional communication in the professional training of foreign language teachers (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the problem of professional communicative culture. The attempt of analyses of ways of professional culture formation by means of foreign languages has been made.
Keywords: professional communicative culture; ways of formation; foreign languages